PENERAPAN METODE TALKING CHIPS DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN PRESTASI BELAJAR PROFESI KEPENDIDIKAN II PADA MAHASISWA PRODI PENDIDIKAN BIOLOGI SEMESTER VB IKIP-PGRI MADIUN - Sri Utami (Jurnal Pendidikan, 2013)
Research aims to improve student achievement half of VB Biology Education Program at Teachers' Training College-Madison PGRI courses Professional Education II. This research is Classroom Action Research (CAR ), with V semester students study subjects Prodi education PGRI Biology Teachers' Training College- Madison with a number of 41 students. Collecting data using a test sheet for students and the quality of the data observation sheet for the implementation of learning activities which include faculty and student learning. The results showed an average value of 59.8 in the first cycle, while in the second cycle was 69.9, an increase of 10.1 or 16.88 %. The quality of learning with the application of methods Talking Chips, which includes data quality faculty and students through observation sheet has increased. Data quality faculty activities in the first cycle was 79.1 with an active predicate, while in the second cycle of 91.6 with very active predicate, thus an increase of 12.5 or 15.8 %. The quality of student learning data in the first cycle was 72.7 with an active predicate, while the second cycle of 95.4 with very active predicate, thus an increase of 22.7 or 31.2 %. The conclusions of this research is the application of methods Talking Chips in cooperative learning can improve student learning achievement Profession Kependidikkan half-PGRI Madison VB Teachers' Training College .